2014
DOI: 10.1111/febs.12950
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the bacterial pseudouridine‐5′‐phosphate glycosidase protein family

Abstract: Pseudouridine is a noncanonical C–nucleoside commonly present in RNA, which is not metabolized in mammals, but can be recycled by the unique enzyme family of bacterial pseudouridine glycosidases such as YeiN from Escherichia coli. Here, we present rigorous bioinformatic and biochemical analyses of the protein family in order to find sequences that might code for nonpseudouridine glycosidase activities. To date, the only other function reported for the enzyme family occurs during the biosynthesis of the antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 29 publications
(62 reference statements)
0
34
0
Order By: Relevance
“…CM020, that catalyze β-C-riboside formation from D-Rib5P (1) and different naphthoquinones (Supplementary Fig. 7) 53,54,87 . The herein developed idea of modular phosphorylation-glycosylation cascades could be analogously applied to AlnA-type C-glycosynthases, to also harness these enzymes' catalytic proficiency and substrate promiscuity for practical synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…CM020, that catalyze β-C-riboside formation from D-Rib5P (1) and different naphthoquinones (Supplementary Fig. 7) 53,54,87 . The herein developed idea of modular phosphorylation-glycosylation cascades could be analogously applied to AlnA-type C-glycosynthases, to also harness these enzymes' catalytic proficiency and substrate promiscuity for practical synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Indigoidine synthetase genes have been engineered and introduced into living systems to construct a cross-kingdom reporter system 16 , generate blue rose 17 , and produce 2 as a promising water-insoluble dye 18,19 . Interestingly, indigoidine synthetase genes are widely distributed in bacteria, including Actinobacteria and Proteobacteria ( Figure S1), and frequently colocalized with genes encoding enzymes that glycosylate C-5 of 1, leading to the water-soluble blue pigment indochrome 20,21 , and the C-nucleoside antibiotic, minimycin 13 (Figure 1b). As such, indigoidine synthetases are involved in biosynthesis of a broad range of bacterial secondary metabolites.…”
mentioning
confidence: 99%
“…It is known that Ψ and other modified ribonucleosides play an important role in inter-nucleotide bond formation by means of guanyl-specific ribonucleases [42] . Ψ is also known to bind protein phosphatase in some bacterial species [43] , [44] , [45] . Previous research has also indicated the importance of Ψ in regulating neuronal functions [46] , which is corroborated by the enrichment of biological processes shown in Fig.…”
Section: Discussionmentioning
confidence: 99%